Receptor mechanism producing a sweet taste from plant aroma compounds - Horie, Fuyumi; Sanematsu, Keisuke; Yasumatsu, Keiko; Hirokawa, Takatsugu; Shigemura, Noriatsu; Yamashita, Atsuko; Kusakabe, Yuko (Scientific reports, 2025)
Fruits and vegetables contain highly volatile hydrophobic small molecules responsible for their aroma, taste, and pungency. Empirically, we understand that these compounds can evoke a sweet taste; however, their specific interactions with sweet taste receptors are unclear. To address this issue, HEK293 cells expressing human and mouse sweet taste receptors TAS1R2/TAS1R3 were used to identify trans -2-hexenal (a novel sweetener) in human and cinnamyl alcohol (a sweetness inhibitor) in mice. The effects of these compounds on TAS1R2/TAS1R3 in humans and mice were evaluated alongside known hydrophobic sweet compounds, and the results showed that they elicited responses in human TAS1R2/TAS1R3 but not in mice. Conversely, some compounds inhibited the sweetness of sucralose both in vitro and in vivo. Response analysis using human and mouse chimeric TAS1R2 and point mutants of TAS1R2 using docking simulations indicated that these compounds bind to the transmembrane domain of TAS1R2 and that multiple amino acid residues are essential to generate a sweet taste. These results indicate that highly volatile hydrophobic compounds generate aroma and sweetness through a different mechanism than hydrophilic sweeteners, such as sucrose.